Overview of the Implementation of the Early Warning Alert Response System (EWARS) at the Suak Ribee Public Health Center, West Aceh District - Mardi Fadillah; Onetusfifsi Putra; Perry Boy Chandra Siahaan (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
The Early Warning Alert and Response System (EWARS) is an important system for early detection and response to extraordinary events (KLB) in health facilities. The Suak Ribee Public Health Center has implemented EWARS, but evaluation of its implementation and operational challenges is still needed. This study aims to analyze the accuracy and completeness of EWARS reporting at the Suak Ribee Public Health Center and to identify challenges and strategies for improving the quality of the system. A descriptive study was conducted through observation and interviews with surveillance officers at the Suak Ribee Public Health Center. EWARS report data for the 2022–2024 period were analyzed quantitatively for accuracy and completeness, and qualitatively to identify obstacles and recommendations for improvement. The accuracy and completeness of reporting reached 100% every year, demonstrating the consistency and effectiveness of the reporting system. The main challenges encountered are limited internet connectivity and funding support, which could potentially affect the sustainability of the system. Improvement strategies include implementing a hybrid offline-online reporting system, increasing human resource capacity through training and clear SOPs, and collaborating with the Health Office, NGOs, and the private sector for operational and funding support. Although reporting is already optimal, improvements in infrastructure, funding, and human resource capacity are still needed to maintain the sustainability of EWARS. The implementation of these strategies can strengthen the surveillance system, support early detection, and improve the response to outbreaks in the working area of the Suak Ribee Public Health Center.